The Qur’ān and Sunnah as a conceptual foundation of Islamic architecture - Omer, Spahic (The Islamic Cultural Center and London Central Mosque, London, 2019)
This article discusses the theme of the Qur’ān and Sunnah as a conceptual foundation of Islamic architecture. It concludes that Islamic architecture is the type of architecture that is inspired and guided primarily by the teachings and belief system of Islam. Islamic architecture in its capacity as a physical locus of life, which to Muslims signifies a form of worship (‘ibādah), is a framework for the implementation of Islam as a complete code of human existence. The Qur’ān and Sunnah, as the divine and eternal sources of Islam and Islamic civilization, it follows, ought to play a foremost role in shaping the conceptual disposition of Islamic architecture. Such roles in this article are summed up as follows: the Qur’ān and Sunnah and adequate perception of the world of architecture, the Qur’ān and Sunnah as the sources of architectural inspiration and catalysts for creativity, averting the vices often associated with architecture, and Prophet Muḥammad (pbuh) and the creation of the city of Madinah. In order to give an extra emphasis to the importance of the subject in question, the topics of the meaning and significance of true Islamic architecture, and the state of Islamic architecture literature, are firstly elucidated. Against that backdrop, the core and main thrust of the article is then approached and discussed. The nature of the article, along with its content, methodology and conclusions, is conceptual and philosophical, rather than empirical.